Factors associated to maternal and child's health in Rio Grande do Sul, Brazil - Franciele Mattei; Ioná Carreno
Abstract Objectives: to analyze the factors associated to maternal and child's health from the Live Births Information System (Sinasc) in Rio Grande do Sul, 2012. Methods: a cross-sectional ecological study with analysis on Sinasc variables from 19 Regional Health Coordinations in Rio Grande do Sul. The variables occurrence frequencies were calculated and analyzed by Spearman correlation. Results: we observed that a higher maternal level of education, the presence of a partner and the adequate number of prenatal consultations reduced the frequency of vaginal delivery, as for the proportion of cesarean section, it was 62%. The frequency of low schooling was associated to prematurity (rho = 0.521, p=0.022) and low birth weight (rho = 0.542, p=0.016). The low prenatal coverage correlated positively with the Apgar score ≤ 7 in the 5th minute (rho = 0.467; p=0.044) and negatively with adequate birth weight (rho = -0.500; p=0.029). Conclusions: this study allows to identify factors associated to maternal and child's health contributing information to the development of actions that qualifies pregnant women's healthcare.